FUNCTIONAL CORRELATIONS BETWEEN LINGUAL KNOWLEDGE AND PSYCHOLOGICAL FEATURES OF PERSONALITY DURING THE PROCESS OF LINGUAL-THINKING ACTIVITY - Лавриненко, Олександр (Current Issues of Foreign Philology, 2021)
This article represents the theoretical empirical research of human inner cognitive processes, connected with thinking and speech activity. The research unites in its plot the philological and psychological paradigms. In the theoretical part the general view and analysis of human speech-thinking processes is conducted, which provide the perception, keeping of new information by individual, its mental processing and future reproduction. The author reflected views to the described problematic of the set of famous philologists and psycholinguists: N. Homsky, L. Vygotsky, A. Leontev, A. Luria, J. Anderson and others. Due to the results of the mentioned theoretical analysis of cognitive processes, directed for perception, keeping, processing and reproduction of any type of lingual information the author achieved to define the lexical-subject relations between the notions like lingual knowledge, linguistic knowledge, encyclopedic knowledge and derivational knowledge. In the practical part of this research the set of psychological and psycholinguistic methodic was applied in order to search the correlations between the psychological features of personality and the peculiarities of its cognitive processes functioning, directly or indirectly connected with the lingual activity. In the result of the mathematical processing of the gathered statistical data the several functional correlations were found between such psychological human features as neuroticism, shyness, sociability, cognitive motive, peculiarities of communal behavior, motivational and emotional spheres structure and the specifics of course of processes, that are connected with the formation and accumulation of lingual knowledge and its qualitative transition to the level of lingual competence. The disclosed tendencies and patterns in the mentioned aspect may can act as elements of empirical foundation in the future creation of new personality-oriented methodic of foreign language teaching. Besides, the disclosed facts can have certain use for creation of new models and theories of human cognitive processes.